Periprocedural imaging and outcomes after catheter ablation of atrial fibrillation. Issue 23 (31st July 2014) - Steinberg, Benjamin A; Hammill, Bradley G; Daubert, James P; Bahnson, Tristram D; Douglas, Pamela S; Qualls, Laura G; Pokorney, Sean D; Calkins, Hugh; Curtis, Lesley H; Piccini, Jonathan P
Abstract : Objective: Catheter ablation of atrial fibrillation (AF) has become an increasingly safe and effective therapy. This has been partly attributed to the use of adjunctive imaging modalities. We aimed to describe the use and associated outcomes of periprocedural imaging for AF ablation. Methods: We studied all Medicare fee-for-service claims for AF ablation from July 2007 to December 2009, and identified associated imaging studies before and during ablation, including transoesophageal echocardiography (TEE), intracardiac echocardiography (ICE), CT and MRI. The primary outcomes were death, stroke or transient ischaemic attack (TIA), repeat ablation, and bleeding (pericardial or vascular) at 6 months. Results: 11 525 patients underwent AF ablation during the study period. There was significant variation in imaging use at the practice level. In addition to electroanatomic mapping, 53% (n=6060/11 525) underwent TEE, 67% (n=7715/11 525) received ICE, and 50% (n=5724/11 525) underwent a preprocedure CT or MRI. Imaging generally increased from 2007 to 2009. After adjustment, the use of preablation CT or MRI was associated with a significantly lower risk of stroke or TIA (0.4% vs 0.9%, adjusted HR 0.46, 95% CI 0.28 to 0.74, p=0.002), and the use of ICE was associated with a lower risk of repeat ablation (5.7% vs 8.5%, adjusted HR 0.59, 95% CI 0.37 to 0.92, p=0.02) but higher risk of bleeding (1.1% vs 0.7%, adjusted HR 1.76, 95% CI 1.15 to 2.70, p=0.009). Conclusions: Periprocedural imaging for AF ablation is increasingly used, although practice patterns vary widely. Our data suggest that periprocedural imaging is associated with better outcomes after catheter ablation; however, prospective studies of periprocedural imaging strategies are warranted.